(untitled) (Tanzania Medical Journal, 2023)
Background Limited involvement of male partners in Birth Preparedness and Complication Readiness (BPCR) is one among other factors behind high maternal mortality rate in Low- and Middle-Income Countries (LMIC). This study aimed at establishing the magnitude and determinants of male partners’ participation in BPCR in two selected districts in Mwanza region, Northwestern Tanzania. Methods In August 2019, a community based cross-sectional study was conducted in Magu and Misungwi districts in Mwanza region. Data were collected from 345 male respondents whose partners had given birth in the one year before the study. An interviewer-administered questionnaire was used to collect information on various components of BPCR. Univariate and multivariate analysis of factors associated with male partners’ participation in BPCR were conducted. Results More than three quarters of male partners adequately participated in BPCR (76%) and the findings were comparable between the two study areas (χ²=0.01; p=0.979). The odds of male participation in BPCR were nine times higher among the married men (aOR =9.06; 95% CI: 4.12-19.96; p<0.001) as compared to those cohabiting and eight times likely among those who were aware of BPCR as a general term (aOR = 8.15; 95% CI: 3.73-17.77; p<0.001). Respondents who discussed with their female partners regarding BPCR had four times higher odds of participating (aOR=4.10; 95% CI: 1.79-9.36; p<0.001) than those who never had conversation. Respondents whose female partners delivered in health facility had seven times higher odds of participating (aOR = 7.60; 95% CI: 2.06-28.04; p=0.002) than those delivered at home. Conclusion The level of participation on BPCR among male partners was high and comparable between the two study areas. Married couple, awareness, discussion with female partners and health facility delivery predicted male participation in BPCR. Therefore, intervention targeting at knowledge and awareness improvement as well as couple discussion empowerment could markedly expand male participation in BPCR.